The Effect Of Good Corporate Governance and Capital Structure on Financial Performanve Empiris Study on Consumtion Industrial company year Periode (2015-2017). - ANDRY MULYADI; KARTIKA HENDRA TITISARI; SITI NURLAELA (JURNAL WIDYA GANECWARA, 2019)
This study aims to examine and analyze the effect of Good Corporate Governance as measured by institutional ownership, audit committee, and capital structure on financial performance. This study uses a sample of 23 manufacturing companies in the consumer goods industry sector that have been listed on the Indonesia Stock Exchange (BEI) in 2015-2017. The data analysis technique used is the classical assumption test, and multiple linear regression analysis. The results of the analysis show that financial institutional ownership, leverage and capital structure affect financial performance. While the audit committee has no effect on financial performance. Simultaneously institutional ownership, audit committee, leverage and capital structure influence financial performance.